PENGARUH FILTER AKTIF DENGAN PENGATURAN DAYA REAKTIF TERHADAP EFISIENSI TRAFO BERBASIS SIMULINK - IK Satriya Dhinata; AAG Maharta Pemayun; IB Gede Manuaba (Jurnal SPEKTRUM, 2021)
Harmonic distortion usually occurs due to the operation of excessive non-linearelectrical loads, this distortion can be reduced by utilizing an active harmonic filter which canusually be adjusted for reactive power on the filter. In this study, an analysis of reactive powersettings on the active filter was carried out to determine the efficiency value obtained byfollowing the IEEE 519 - 2014 THDi standard value of 8% for each phase. The results of theanalysis of the smallest reactive power setting but exceeding the transformer efficiency valuewhen the existing condition meets the IEEE 519 - 2014 standard is 40 % with the THDi value forthe R phase = 7, 54%, S = 7,74%, and T = 7, 37% obtained an efficiency value of 96, 31%.